Theoretical investigation of boundary slip on the hydrodynamic lubrication performance in pocketed bearings including cavitation. (2017) - Muchammad, M.; Tauviqirrahman, Mohammad; Pratomo, Ariawan Wahyu; Jamari, J.; Schipper, Dirk Jan
Boundary slip in bearings is becoming more and more popular to improve the hydrodynamic performance (pressure and shear stress). However, most of previously published works regarding textured bearings neglected the cavitation effect and make their results questionable. The main aim of this paper is to investigate the hydrodynamic performance of slip pocketed bearings considering cavitation by a theoretical approach. Cavitation was of particular interest with respect to pressure generation and shear stress. One main result presented here was that slip over the whole surface could retard the presence of cavitation and therefore the generated pressure and shear stress could be optimal. The work presented here leads to a design reference guideline that could be used by the designer/engineer to design slip pocketed bearings for improving the hydrodynamic performance.